Feminist Translation Strategies in Children’s Literature: A Case Study of Helen Wang’s Translation of Bronze and Sunflower (International Journal of Language, Literacy and Translation, 2025)
In recent years, children’s literature has gained researchers’ attention as a secondary genre. Expounding on the (secondary) status of women, translators, and children’s literature, this study draws on how female translators address the translation of children’s literature by analyzing Helen Wang’s renowned Chinese-English translation of Bronze and Sunflower. There are many studies on this translation from different perspectives, which includes translation strategies. Nevertheless, few studies have approached translation strategies from the lens of feminism. Hence, the present article aims to address two issues by taking Helen Wang’s translation as a case study:1) What feminist strategies did Wang employ when translating this book? 2) Did Wang hereby display feminist consciousness? To this end, Delabastita’s (1993) taxonomy on translation strategies was adopted to analyze the parallel corpus selected from the original work and its translated version. Overall, the analysis uncovered evidence of the use of these five strategies: substitution, repetition, deletion, addition, and permutation, which suggests that Helen Wang had a feminist approach while translating. Through these feminist translation strategies, she intervened in girls’ passive image and women’s secondary status, and erasing the values they violate, hence the demonstration of her feminist consciousness. This study may lead to a greater focus on feminist translation strategies in children’s literature, with its findings providing a reference for researchers in translation as well as for translators of children’s literature. Suggestions for future research are outlined at the end of the article.